1996
DOI: 10.1123/ijsn.6.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Role of Energy Balance in Athletic Menstrual Dysfunction

Abstract: The cessation of menstrual function in the female athlete may reflect her inability to adapt to the environmental and lifestyle stressors associated with training and competition. As society's emphasis on thinness, dieting, and exercise continues to increase, so will the incidence of menstrual dysfunction in active females. Unfortunately, some individuals view athletic menstrual dysfunction as a benign consequence of strenuous exercise. Conversely, it is most likely a strong indicator of overtraining and a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 71 publications
1
27
0
2
Order By: Relevance
“…Mulheres amenorréicas devem ser estimuladas a ingerir pelo menos 1.500mg de cálcio elementar por dia para assegurar um equilíbrio do cálcio 18,36 . A reversão da amenorréia já foi relatada após uma lesão, durante uma redução do treinamento e com um aumento da ingestão calórica 84,[112][113][114][115][116] . Entretanto, não há dados epidemiológicos disponíveis sobre a taxa de sucesso de qualquer alteração do estilo de vida ou tratamento para reverter a amenorréia, aumentar a massa óssea ou a fertilidade 97 .…”
Section: Amenorréiaunclassified
See 1 more Smart Citation
“…Mulheres amenorréicas devem ser estimuladas a ingerir pelo menos 1.500mg de cálcio elementar por dia para assegurar um equilíbrio do cálcio 18,36 . A reversão da amenorréia já foi relatada após uma lesão, durante uma redução do treinamento e com um aumento da ingestão calórica 84,[112][113][114][115][116] . Entretanto, não há dados epidemiológicos disponíveis sobre a taxa de sucesso de qualquer alteração do estilo de vida ou tratamento para reverter a amenorréia, aumentar a massa óssea ou a fertilidade 97 .…”
Section: Amenorréiaunclassified
“…Atletas amenorréicas que utilizam terapia de reposição hormonal em doses utilizadas para mulheres pós-menopausa demonstraram manutenção da DMO mas nenhum ganho 135 . Mulheres com amenorréia e perdas ós-seas mais leves podem preferir ajustar o treinamento e os padrões nutricionais para retornar ao seu ciclo reprodutivo normal 15,18,27,113,114,136 .…”
Section: Osteoporoseunclassified
“…Exercise-induced amenorrhoea is now recognized as a multifactorial disorder in which several factors collectively suppress reproductive function. Amenorrhoea is just a symptom associated with low body weight, low body fat, physical stress, low energy and nutrient intake, energy drain and chronic hormonal alterations (Dueck et al, 1996;Marcos et al, 1998;West, 1998).…”
Section: Eating Disorders In Sportsmentioning
confidence: 99%
“…Contrary to popular belief, menstrual irregularities do not indicate optimal body fat or training levels. While cessation of menstruation may be viewed by some as convenient, it can be detrimental to bone health and may have long-term consequences resulting in infertility and other reproductive problems, impaired immune function, and an increased risk for cardiovascular diseases (Dueck et al, 1996).…”
Section: Eating Disorders In Sportsmentioning
confidence: 99%
“…This lack of knowledge or awareness may explain why many athletes inadvertently develop a negative calorie balance and amenorrhea. Dueck et al 14 reported that the average calorie difference between amenorrheic and eumenorrheic athletes was only a deficit in caloric balance of 250 kcal per day. This is the caloric equivalent of 3 glasses of skim milk or a single candy bar, and represents less than 10% of total caloric intake for an active athlete.…”
Section: Physiological Consequences Of Low Caloric Intakementioning
confidence: 99%